Víctimas de trata de seres humanos con fines de trabajo forzoso como sujetos de especial protección - Cotrina Gulfo, Cotrina Gulfo (Corporación Universitaria Americana, 2023)
In the immense tapestry that is history and humanity, dark specters and uncertain contours emerge that delineate a harrowing reality in our contemporary context: human trafficking. Scientific and socio-legal approaches to this intricate phenomenon, while essential to the range of universal values, are often insufficient to fully unveil its roots and manifestations. This book, then, emerges as an attempt to undertake both a philosophical and legal study to critically review trafficking, an evil whose deplore echoes from an immemorial past.